Sero-prevalence of Hepatitis B virus infection among tribal under-five children in aspirational Nabarangpur district of Odisha, India - Prakash Kumar Sahoo; Gayatree Nanda; Abhinav Sinha; Sanghamitra Pati (Elsevier, 2023)
Introduction: Hepatitis B (HB) is a major global health problem and a leading cause of chronic Hepatitis, liver cirrhosis, and hepatocellular carcinoma. Determining the prevalence of serological marker/s will help to know the burden of this disease and further carry out proper management. This study aimed to assess the seroprevalence of HBV infection among the tribal under-five children of Nabarangpur district, Odisha, India. Methods: A community based cross-sectional study was carried out employing multistage systematic random sampling. Serum samples were collected from 263 children. The participants were tested for Hepatitis B surface antigen (HBsAg) using Enzyme linked Immunosorbent Assay (ELISA). Descriptive statistics such as frequency and proportions were used to report the findings. Results: We observed 3 (1.14%) children to be positive for HBsAg. The prevalence of HBsAg was higher (1.63%) among females. Conclusion: The sero-prevalence of hepatitis B infection among under-five children was notably low in Nabarangpur district. This highlights the importance of vaccination coverage and further warrants information, education and communication to continue motivating people to uptake vaccines against the infection.